2017
DOI: 10.1002/mma.4629
|View full text |Cite
|
Sign up to set email alerts
|

Optimal bed net use for a dengue disease model with mosquito seasonal pattern

Abstract: MOS Classification: 92D30; 34A34; 49J15Controversial results concerning the effectiveness of bed net in reducing dengue fever transmission make further research necessary in this direction. At this aim, we consider a mathematical model of dengue transmission where the use by individuals of insecticide-treated bed nets is taken into account, combined or not with insecticide spraying. Furthermore, as climatic factors play a key role in mosquito-borne diseases, we model the effect of seasonality through a periodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 51 publications
(108 reference statements)
2
29
0
Order By: Relevance
“…9 (f), the prevention is kept at full effort for approximately 37 days and then reduces gradually till the end of the intervention, while the insecticide is maintained at maximal effort during 69 days and then reduces rapidly for the rest of the intervention. These results are in accord with earlier studies [36] , [43] which showed when the two controls were combined, the impact of insecticide spraying appeared to be dominant over preventive measures alone. Moreover, the prevalence timing was similar to that of insecticide-only interventions.…”
Section: Numerical Results Of the Control Problemsupporting
confidence: 92%
See 1 more Smart Citation
“…9 (f), the prevention is kept at full effort for approximately 37 days and then reduces gradually till the end of the intervention, while the insecticide is maintained at maximal effort during 69 days and then reduces rapidly for the rest of the intervention. These results are in accord with earlier studies [36] , [43] which showed when the two controls were combined, the impact of insecticide spraying appeared to be dominant over preventive measures alone. Moreover, the prevalence timing was similar to that of insecticide-only interventions.…”
Section: Numerical Results Of the Control Problemsupporting
confidence: 92%
“…The control insecticide spraying only has been considered in dengue control model given in [42] . The use of both the control for dengue control in the population is considered in [36] , [43] . The prevention efforts include the use of mosquito nets, mosquito repellent like DEET, and treat clothes with repellent, while insecticide includes spraying and fogging against mosquitoes.…”
Section: Optimal Control Problemmentioning
confidence: 99%
“…Since ancient times, the prevalence of infectious diseases has brought enormous damage to people; therefore, many countries around the world pay more attention to the investigation of the infectious diseases. Various epidemic models have been proposed and analyzed for prevention and control strategies, especially for vector borne diseases 1‐3 …”
Section: Introductionmentioning
confidence: 99%
“…Female mosquitoes, however, play a role in the transmission of the disease and are principal target for most control strategies. Dengue models which include mosquito dynamics explicitly [5,14,15,31,36] add compartments for susceptible and dengue-infected mosquitos. The vector population is governed by a susceptible-infected model because the mosquitos do not recover from the virus.…”
Section: Introductionmentioning
confidence: 99%
“…The vector population is governed by a susceptible-infected model because the mosquitos do not recover from the virus. Control strategies for models of single-strain dengue with seasonality have been studied in [5,31] and for a two-strain model without seasonality in [36].…”
Section: Introductionmentioning
confidence: 99%